Cluster Model Study of the Indonesian Defense Industry towards Encouraging Industry Independence - Sita Deliyana Firmialy, Sri Hartati, Ade Muhamad,; Tasrif, Muhamad (Opción, 2019)
The purpose of this research is to find out how the defense industry and stakeholders are involved in developing defense industry clusters via comparative qualitative research methods. The results of the research show that the defense industry sector has 4 cluster stages. In conclusion, in the medium term, increasing industrial competitiveness is carried out by building and developing priority industry clusters while in the long run, it is more focused on integrating cluster approaches with efforts to manage demand (management demand) and build core competencies in each cluster.